The Influence of Polychlorinated Biphenyls Contamination on Soil Protein Expression. (4th December 2013) - Zhang, Xi; Li, Feng; Liu, Tingting; Peng, Cheng; Duan, Dechao; Xu, Chen; Zhu, Shenhai; Shi, Jiyan
Abstract : Polychlorinated biphenyls (PCBs) are typical representative of chlorinated organic pollutants. Given the toxicity of PCBs, there is an urgent need to select an appropriate indicator to monitor their biological effects on soil ecosystems. For this purpose, we investigated the impacts of PCBs on soil protein and the potential of using protein as a biological indicator to assess soil contamination due to PCBs. This study demonstrated that soil protein concentration and expression were negatively affected by PCBs. In addition, significantly (P < 0.01 ) negative correlation was observed between protein concentration and PCBs. Subsequently, protein size distribution separated by SDS-PAGE revealed that with the increase in PCBs concentration there are less large molecular weight proteins and more low molecular weight proteins (< 40 kD). Consequently, soil protein level has the potential to be an indicator of soil contamination, and these low molecular weight proteins have significant meaning for getting insight into the ecological effects of PCBs on the soil environment.